NILAI-NILAI SIGNIFIKAN MASYARAKAT LOKAL TERHADAP PELESTARIAN PUSAKA PASCABENCANA DI BANDA ACEH - Zya Dyena Meutia; Roos Akbar; Denny Zulkaidi; Sri Maryati (Jurnal Al-Bayan: Media Kajian dan Pengembangan Ilmu Dakwah, 2019)
In the last few decades, there has been a shift in the sense of heritage from the thought of "how to ensure an heritage object will not be destroyed" into "what values an heritage object has and how best to preserve these heritage values". Many studies and researches on heritages in urban areas have been carried out, but not many have discussed more deeply about the characteristics of significant heritage values as a consideration in determining urban heritage. Heritage values that are inherent are only considered by perception experts and the government toward heritage usual as a temple, site the kingdom and historic buildings have hundreds of years age. While the perspective of comprehensive values and consideration of values from the heritage is one of the important factors in success preservation of heritage areas in urban areas. This study intends to uncover significant values that into consideration in preserving heritage post disaster in the urban heritage and in designating an object and place as a heritage. This study uses a constructivist paradigm with an interpretive approach because it attempts to construct the existence of significant cultural values in the public perception of seeing an area as an inheritance. The result is show the most important significant values for them, namely religius, memory, history, traumatic, resilience and social. Keywords: significant values, heritage, religius, local community